Phubbing Behavior and Quality of Friendship in Faculty of Public Health, Nusa Cendana University - Maria Sindisari Parus; Apris Adu; M. K. P. Abdi Keraf (Journal of Health and Behavioral Science, 2021)
Phubbing is a behavior or act of ignoring someone in the scope of the social environment by focusing on smartphones instead of paying attention to the interlocutor when interacting so that it affects interpersonal relationships. This study aims to determine the effect of phubbing behavior and the quality of friendship among students of the Faculty of Public Health, Universitas Nusa Cendana Kupang. This research method uses quantitative research with a simple linear regression analysis design. The number of samples was 100 students of the Faculty of Public Health, Universitas Nusa Cendana Kupang. The sampling technique used was simple random sampling. The results of this study indicate that the significance value (sig) is 0, 033 <of 0.05 and the value of t count> t table is -2.162> 1.984. This means that Ho is rejected and Ha is accepted that there is a negative effect of phubbing behavior on the quality of friendship among students of the Faculty of Public Health, Universitas Nusa Cendana Kupang.